Prevalence of human T cell leukemia virus-I (HTLV-I) antibody among populations living in the Amazon region of Brazil (preliminary report) - NAKAUCHI, C. M. (2015)
Prevalence of human T cell leukemia virus-I (HTLV-I) antibody among populations living in the Amazon region of Brazil (preliminary report)NakauchiC. M.LinharesA. C.MaruyamaK.KanzakiL. I.MacedoJ. E.AzevedoV. N.CassebJ. S. R. Fundação Serviços de Saúde Pública, Seção de Vírus, Instituto Evandro Chagas Belém Brasil Chiba Cancer Research Institute, Department of Pathology Chiba Japan Universidade Federal do Pará Belém Brasil Instituto Offir Loyola Belém Brasil Faculdade Estadual de Medicina Belém Brasil 0319908512933Forty-tree (31.4%) out of 137 serum samples obtained from two Indian communities living in the Amazon region were found to be positive for HTLV-I antibody, as tested by enzyme-linked immunosorbent assay (Elisa). Eighty-two sera were collected from Mekranoiti Indians, yielding 39% of positivity, whereas 11 (20.0%) or the 55 Tiriyo serum samples had antibody to HTLV-I. In addition, positive results occurred in 10 (23.2%) out of 43 sera obtained from patients living in the Belem area, who were suffering from cancer affecting different organs. Five (16.7%) out of 30 Elisa positive specimens were also shown to be positive by either Western blot analysis (WB) or indirect immunogold electron microscopy (IIG-EM).